Measuring IPv6 performance in a newly deployed IPv6 campus network - Sajat, Mohd Samsu; Ahmad, Adi Affandi; Ahmad, Amran; Hanis, Ahmad (2015)
The implementation of IPv6 in dual-stack environment at Universiti Utara Malaysia campus network has been done successfully but how it performs compared to IPv4 has yet to be measured.A study on the performance of IPv6 network has been done to measure this performance.The study employed a simple performance measurement/testing using ping to a number of IPv6 enabled web servers.The RTT of the ping packets for both IPv4 and IPv6 is compared to see the performance of IPv6 network compared to IPv4 in a dual-stack environment. The study has found that the IPv6 network performance is slightly worse than IPv4 due to some reasons.This paper discusses some of the findings.